Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm having trouble with part $ii.$ of the following question:

$i.$ Express the following in terms of N and z: $$\sum^N_{n=1}2^{-n}z^n$$

Expanding with geometric series: $$\sum^N_{n=1}2^{-n}z^n \equiv \sum^N_{n=1}\bigg(\frac{z}2\bigg)^n = \bigg(\frac{z}2\bigg) + \bigg(\frac{z}2\bigg)^2 + \bigg(\frac{z}2\bigg)^3 + ... + \bigg(\frac{z}2\bigg)^N$$ $$= \frac{\bigg(\frac{z}2\bigg)\bigg(1-\bigg(\frac{z}2\bigg)^N\bigg)}{1 - \bigg(\frac{z}2\bigg)} = \frac{z\bigg(1-\bigg(\frac{z}2\bigg)^N\bigg)}{2-z}$$

$ii.$ Deduce that: $$\sum^{10}_{n=1}2^{-n}\sin(\frac1{10}n\pi) = \frac{1025\sin(\frac1{10}\pi)}{2560-2048\cos(\frac1{10}\pi)}$$

Looking instead at the imaginary part of the following series: $$\sum^{10}_{n=1}2^{-n}e^{i\frac{n\pi}{10}} = \frac12e^{i\frac{\pi}{10}} + \frac14e^{i\frac{2\pi}{10}} + \frac18e^{i\frac{3\pi}{10}} + ... + \frac1{2^{10}}e^{i\pi}$$ $$=\frac{\bigg(e^{i\frac\pi{10}}\bigg)\bigg(1-\bigg(\frac{e^{i\frac\pi{10}}}2\bigg)^{10}\bigg)}{2-e^{i\frac\pi{10}}} = \frac{\bigg(e^{i\frac\pi{10}}\bigg)\bigg(1-\frac{e^{i\pi}}{2^{10}}\bigg)}{2-e^{i\frac\pi{10}}}$$

Applying $-e^{i\pi} \equiv 1$ and simplifying, then applying $e^{i\theta}\equiv r(\cos\theta+i\sin\theta)$: $$\implies \sum^{10}_{n=1}2^{-n}e^{i\frac{n\pi}{10}} = \frac{\bigg(e^{i\frac\pi{10}}\bigg)\bigg(2^{10}+1\bigg)}{2^{10}(2-e^{i\frac\pi{10}})} = \frac{1025(\cos\frac\pi{10}+i\sin\frac\pi{10})}{2048-1024(\cos\frac\pi{10}+i\sin\frac\pi{10})}$$


My understanding is that, from the final equation, looking at it's imaginary part we would have to take the $i$ term from the numerator and the real term from the denominator, like so: $$= \frac{1025(\sin\frac\pi{10})}{2048-1024(\cos\frac\pi{10})}$$

But how do I satisfy the denominator to get the required $(2560 - 2048\cos\frac\pi{10})$?

Edit: On second thought, adding $512-1024\cos\frac\pi{10}$ to the denominator does not balance the equation, which means that this is not the correct sum.

share|improve this question

1 Answer 1

up vote 2 down vote accepted

HINT:

$$\frac{\cos t+i\sin t}{2-\cos t-i\sin t}$$

$$=\frac{(\cos t+i\sin t)(2-\cos t+i\sin t)}{(2-\cos t)^2+\sin^2 t}$$

$$=\frac{(2\cos t-1+2i\sin t)}{5-4\cos t}$$

share|improve this answer
    
Okay, simply multiplying $\frac{1025}{1024}$ to your simplification I got the required answer. Thanks a bunch. –  Ozzy Apr 25 '13 at 16:52
1  
@Ozzy, my pleasure. –  lab bhattacharjee Apr 25 '13 at 16:54

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.